Alpha7 nicotinic acetylcholine receptors in lung inflammation and carcinogenesis: Friends or foes?. Issue 9 (30th January 2019) - Hajiasgharzadeh, Khalil; Sadigh‐Eteghad, Saeed; Mansoori, Behzad; Mokhtarzadeh, Ahad; Shanehbandi, Dariush; Doustvandi, Mohammad Amin; Asadzadeh, Zahra; Baradaran, Behzad
Abstract: The lung tissue expresses the cholinergic system including nicotinic acetylcholine receptors (nAChRs) which included in many physiologic and pathologic processes. Mounting evidence revealed that these receptors have important roles in lung carcinogenesis via modulating either stimulatory or inhibitory signaling pathways. Among different members of nicotinic receptors family, alpha7‐subtype of nAChR (α7nAChR) is a critical mediator involved in both inflammatory responses and cancers. Several studies have shown that this receptor is the most powerful regulator of responses that stimulate lung cancer processes such as proliferation, angiogenesis, metastasis, and inhibition of apoptosis. Moreover, aside from its roles in the regulation of cancer pathways, there is growing evidence indicating that α7nAChR has profound impacts on lung inflammation through the cholinergic anti‐inflammatory pathway. Regarding such diverse effects as well as the critical roles of nicotine as an activator of α7nAChR on lung cancer pathogenesis, its modulation has emerged as a promising target for drug developments. In this review, we aim to highlight the detrimental as well as the possible beneficial influences of α7nAChR downstream signaling cascades in the control of lung inflammation and cancer‐associated properties. Consequently, by considering the significant global burden of lung cancer, delineating the complex influences of α7 receptors would be of great interest in designing novel anticancer and anti‐inflammatory strategies for the patients suffering from lung cancer. Abstract : Plasma membrane and intracellular expression of alpha7‐subtype of nicotinic acetylcholine receptor (α7nAChR) and its numerous signaling pathways in the modulation of lung inflammation and cancer progression. Identifying the precise molecular mechanisms of these receptor‐initiated signaling cascades paved the way for effective therapeutic strategies for the lung inflammation and carcinogenesis therapy.